Denial of causality by hume and answer of commentators of transcendent wisdom of Mulla Sadra - Marvinam, Mohsen (Penerbit Universiti Kebangsaan Malaysia, 2020)
Hume divides all propositions into two parts: the relations of ideas and matters of fact. He considers the first part certain and matters of fact that makes us aware of the future and can take us beyond sensory perception are uncertain. He believes all reasoning about matters of fact is based on the relation of cause and effect and the principle of uniformity of nature. Based on his especial epistemology, argues that the principle of causality is a mental habit and the principle of uniformity of nature is matter of facts must be proved by experience that its proof and argument is probable that leads to a circle and ultimately expresses his skepticism. Commentators of transcendent wisdom based on the intuitive knowledge of the soul in its own works and actions, proved the idea of causality. They have discussed the unity of sensory and sensible theory, along with the principle of self-evident of causality that these theories only explain the origin of the concept of causality and its generality. However, the main question is how can causality be attributed to objective instances? In response, we have discussed the combination and sum of reason and sense using the experimental method.